2011
DOI: 10.1007/s00228-011-1089-1
|View full text |Cite
|
Sign up to set email alerts
|

The status of paediatric medicines initiatives around the world—what has happened and what has not?

Abstract: Although much still needs to be done, it's clear that with concerted efforts and appropriate resources, change is possible but slow. Retaining and fostering public and political interest in paediatric medicines is challenging, but pivotal for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 23 publications
(26 reference statements)
0
98
0
2
Order By: Relevance
“…While improvements have occurred, progress has been slow [1]. A study conducted by the FDA in the United States examined different methods of predicting paediatric clearance of drugs based on adult values and concluded that no single method of prediction is suitable for all drugs or age groups [2].…”
Section: Introductionmentioning
confidence: 99%
“…While improvements have occurred, progress has been slow [1]. A study conducted by the FDA in the United States examined different methods of predicting paediatric clearance of drugs based on adult values and concluded that no single method of prediction is suitable for all drugs or age groups [2].…”
Section: Introductionmentioning
confidence: 99%
“…Regulatory authorities avoided giving a license for paediatric use and consequently, clinicians were compelled to use the adult-tested medicines in children as "off-label" [9,19]. This differential attitude towards children led the United States in 1997 to bring in strong legislation to address paediatric needs and to generate paediatric data for medicines [20,21,22] This was followed in 2007, by the European Union's Paediatric Regulation [20,23,24] and the World Health Assembly's adoption of resolution WHA 60.20 which called for better medicines for children in the same year [20,25].…”
Section: Obtaining Paediatric Data For Medicinesmentioning
confidence: 99%
“…The reward/incentive in this case where the medicine is still under intellectual property protection is chiefly a 6-month patent protection which is of great benefit to industry in terms of profit and reputation. For off-patent medicines which are not under intellectual property protection providing paediatric data is voluntary: data protection and some form of public funding for studies are offered as incentives [20,21,22,23,24,25,26,27].…”
Section: Obtaining Paediatric Data For Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel and locally applicable knowledge translation and dissemination activities must be identified and put in place, in order to ensure that essential information reaches all the aforementioned in a timely and efficient manner, regardless of geographical, technological, and/or other barriers. Professional organizations can be pivotal in recognizing the importance of disseminating information pertaining to pediatric care, and could help in a significant way to advance these goals [40,41].…”
Section: Knowledge Transfermentioning
confidence: 99%